Effect of Feeding Chitin on Poultry - K.G., Ramachandran nair; P.T., Mathew; P., Madhavan; P.V., Prabhu (Fishery Technology, 2025)
Chitin in 0.25 and 0.5% level incorporated in a commercial poultry feed (control) was fed to broiler chicks and the weight gain was studied in comparison with control feed. The birds fed on diet containing 0.5% chitin showed significant increase in weight and decrease in feed conversion ratio. Analysis of the data showed that addition of 0.5% chitin in the commercial diet resulted in doubling the profit of the farmer. Weight gain with feed containing 0.25% chitin was not significant and also not economically beneficial compared to control. Similar studies conducted on white leghorn layers showed a drop in egg production in birds fed on diets containing 0.5% chitin compared to control diet.